Creation of a knowledge management process in broiler production of Thailand - Injana, W.; Phonpakdee, R.; Poungsuk, P.; Petsangsri, S. (My University, 2019)
The Delphi technique is employed in this study to find an appropriate process of knowledge management in broiler production of Thailand. It is a specific agricultural knowledge management, which is different from other types of knowledge that are mostly accumulated knowledge gained from practice and problem solving. Different factors based on current situation are used to select an appropriate process with tacit knowledge management. It can aid problem solving in practice as the explicit knowledge can be transferred and connected to a method of cause analysis and thus address challenges related to broiler production. This helps develop the production system and knowledge transfer to benefit a new generation of animal husbandry practitioners. Results of the study show that the creation of the knowledge management process in broiler production involved seven steps: knowledge indication, knowledge creation and acquisition, knowledge codification and refinement, systematic knowledge management, knowledge access knowledge sharing, and learning process. A very high level ofconsistency in the value of opinions of specialists on knowledge management was found. Specific knowledge must be kept to construct innovative ideas for broiler production and development. This is to ensure safe food production and food security support, which results in sustainable production of safe meat.
Keywords: Broiler production; Knowledge management; Sustainability